Extensively drug-resistant tuberculosis treated with bedaquiline: A case report in the particularly vulnerable tribal group of Madhya Pradesh, India - Prashant Mishra; R Sharma; R Yadav; Gaurav Bansal; V G Rao; Jyothi Bhat (Wolters Kluwer Medknow Publications, 2021)
The management of drug-resistant (DR) tuberculosis (TB) remains a challenge particularly in remote rural areas of the country. Although the treatment with wholly oral drug regimens, including bedaquiline (BDQ) and delamanid, is rolled out under the National TB Elimination Program, little is known about its coverage and the effectiveness in hard-to-reach tribal areas. The present report describes the early identification and successful management, through team effort, of a case of extensively DR TB belonging to the Saharia tribe - a Particularly Vulnerable Tribal Groups (PVTGs) of Madhya Pradesh, which has a very high prevalence of TB. The BDQ-containing regimen was well tolerated and found effective with minimal side effects and contributed to the reduced time to culture conversion and radiological improvements. The concerted efforts and strategies need to be adopted for effective implementation of Programmatic management of DR TB (PMDT) guidelines in remote tribal areas of the country.